1994
DOI: 10.1071/ea9940105
|View full text |Cite
|
Sign up to set email alerts
|

Hatching, motility, and infectivity of root-knot nematode (Meloidogyne javanica) following exposure to sodium hypochlorite

Abstract: The potential for disinfestation of root-knot nematode (Meloidogyne javanica) in irrigation water and hydroponic growing media using sodium hypochlorite was assessed by studying its effects on hatch, motility, and infectivity of the nematode. When eggs of M. javanica were exposed to 200-10000 pg available chlorine/mL for 5 min-24 h, hatch and infectivity of second-stage juveniles (J2s) were unaffected. However, exposure of eggs to 50000 or 125000 �g available chlorine/mL for >1 h reduced hatch during the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Serious phytotoxicity occurred at concentrations above 50 ppm, and 15 to 25 ppm seemed the best in terms of balancing good bacterial wilt control with minimal phytotoxicity. There is also evidence showing that NaOCl is effective against root-knot nematodes in hydroponic systems [89]. Chloramine and chlorine dioxide (ClO 2 ) are two other chlorine-based disinfectants which have only rarely been used in hydroponic or recirculation systems.…”
Section: Chlorinementioning
confidence: 99%
“…Serious phytotoxicity occurred at concentrations above 50 ppm, and 15 to 25 ppm seemed the best in terms of balancing good bacterial wilt control with minimal phytotoxicity. There is also evidence showing that NaOCl is effective against root-knot nematodes in hydroponic systems [89]. Chloramine and chlorine dioxide (ClO 2 ) are two other chlorine-based disinfectants which have only rarely been used in hydroponic or recirculation systems.…”
Section: Chlorinementioning
confidence: 99%
“…When J2s were exposed to >2 g accessible chlorine/ml for >24 hours, their motility and ability to generate galls were eliminated (Wood and Foot, 1975). A study that applied sodium hypochlorite to irrigation water and hydroponic growing media to control RKN (M. javanica) concluded that the nematode's hatch, motility, and infectivity were not affected (Stanton and O'Donnell, 1994), Perhaps the concentration of the applied disinfectant was low in order to prevent negative effects on growing plants.…”
Section: Virkon S Nematicidal Effect On M Incognita Reproduction and ...mentioning
confidence: 99%